SA-10 Surgical Approaches to Feline Mammary Tumor and Abdominal Mass - Nimas Ayu Pertiwi (Hemera Zoa, 2018)
Mostly the feline mammary tumors are malignant tumors, the ratio or percentage of malignant mammary tumors is higher in cat (86%) as compared to dog (42%) and the histology of feline mammary tumors is closer to that in human breast cancer[1]. Adenocarcinomas are the second frequent tumor in cats, followed by mast cell tumor. Gastrointestinal stromal tumor (GIST) are thought to originate from the interstitial cells which from a network that coordinates peristalsis in gastrointestinal tract. These occur most frequently in the jejunum, caecum and colon[2]. Abdominal radiography image and histophatological examination helped to diagnose and the way to decide the treatment.